Obstructive sleep apnea syndrome predictors in truck drivers - Medeiros, Clarissa Mari de; Nakashima, Erika; Feijó, Esmeralda; Bonnet, Fabianne; Silva, Luana Sarti e; Gandra, Lyvia Lorena (Saúde Ética & Justiça, 2016)
Traffic accidents are one of the leading causes of worldwide morbidity and mortality. Studies show that about 20% of these accidents are due to the lack of attention and/or excessive sleepiness. Drowsiness can be considered a potential indicator of Obstructive Sleep Apnea Syndrome (OSAS) when combined with overweight or obesity, high blood pressure and enlarged Cervical Circumference (CC). Studies suggest that professional drivers have a higher prevalence of OSAS than the general population, which is a matter of concern for traffic safety. Nevertheless, only in a few European countries is the subject of OSAS included as part of drivers’ license regulation criteria. In Brazil, Resolution 425 of 11.27.2012 specifically refers to the evaluation of sleep disorders, including its parameters. Since 2006, a project was initiated called the “Highway Health Command” (HHC), that consists of educational blitzes with spot surveys on Brazilian roads, in order to detect risk factors in truck drivers’ health. Thus, during the HHC held in two cities of São Paulo in 2014, data obtained from examinations and questionnaires were used for this observational and cross-sectional study, aiming to estimate the prevalence of OSAS predictors in truck drivers in São Paulo state (Brazil). Results showed that the indicators fell short of the desirable standards. High blood pressure showed deviations in more than ¼ drivers; body mass index greater than 30kg/ m² was noticed in 29.5% participants; CC was larger than 45cm in 6% drivers and 5.7% participants scored 12 or more at Epworth Sleepiness Scale (ESS). This study forewarns of the severity of drowsiness in national highways, emphasizing the need for progressive inclusion of this disease among medical conditions to which specific attention should be given in examinations of traffic medicine and drivers’ health.